2023
DOI: 10.1038/s41598-023-37380-x
|View full text |Cite
|
Sign up to set email alerts
|

Spouse’s coping strategies mediate the relationship between women’s coping strategies and their psychological health among infertile couples

Abstract: Social problems and suffering from the treatment process for infertile couples, especially for women, require the couples to cope with them to balance the infertility crisis. According to the close interactions of the couples with each other, the objective of the present study was to explore a theoretical framework for the relationships between women’s coping strategies, spouses’ coping strategies, and women’s psychological health in infertile couples who were candidates for assisted reproductive technology (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Maladaptive coping strategies may not positively affect psychological health among infertile couples [ 31 ]. It is also important to note that women’s self-blame and self-focused rumination strategies have a negative impact on women’s psychological health [ 32 ]. In a study by Pedro, it was reported that infertile women had difficulties with friends with children and often experienced social withdrawal at social functions such as family and friends’ gatherings due to feelings of being marginalized [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maladaptive coping strategies may not positively affect psychological health among infertile couples [ 31 ]. It is also important to note that women’s self-blame and self-focused rumination strategies have a negative impact on women’s psychological health [ 32 ]. In a study by Pedro, it was reported that infertile women had difficulties with friends with children and often experienced social withdrawal at social functions such as family and friends’ gatherings due to feelings of being marginalized [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since infertility is a couple-based problem, each partner’s psychological conditions and coping strategies might affect the other partner’s coping and mental health 14 .…”
Section: Introductionmentioning
confidence: 99%